A 45-YEAR-OLD MAN WITH CHRONIC HEART FAILURE: CASE REPORT (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
Chronic heart failure is a disorder in which the heart muscle weakens and results in heart failure in pumping and supplying enough blood needed by the body. Factors that cause heart failure are very diverse, including smoking habits, diabetes mellitus, hypertension, hyperlipidemia, being overweight and stress. In this case, it was reported that a 45-year-old man came to the emergency room with complaints of shortness of breath since four days ago, aggravated by light activities such as walking to the bathroom, cold sweats, coughing at night, and swelling in both legs. The patient had the same complaint six months ago and was admitted to the hospital. However, the patient did not take the medication. History of hypertension recognized by the patient, but not controlled. Physical examination found Body Mass Index 27.7 (obese), blood pressure 178/104 mmHg, pulse rate 114 times/minute regular, respiratory rate 30 times/minute, Oxygen Saturation 92%. Jugular venous pressure increased 5+4 cm. Percussion of the heart reveals an enlarged heart border, auscultation of the heart reveals S3 Gallop, accompanied by heart murmurs. Lung examination revealed moist crackles in both lungs. Examination of the extremities revealed pitting edema in both legs. Electrocardiography examination found sinus tachycardia with and Couplet Ventricular Extra Systole. Chest X-ray examination showed cardiomegaly and early features of pulmonary edema. Echocardiography results showed global hypokinetic, decreased left ventricular and right ventricular systolic function, left ventricular ejection fraction 30.1%, left atrial and ventricular dilatation, concentric and eccentric left ventricular hypertrophy, moderate mitral regurgitation, moderate tricuspid regurgitation, severe pulmonary hypertension. Patients were given intravenous injections of Furosemide 40 mg every 8 hours, Ramipril tablets 1x10 mg, Digoxin tablets 1x0.25 mg, Nitrokaf Retard tablets 2 x2.5 mg, and Spironolactone tablets 1 x25 mg
Keywords: chronic heart failure; shortness of breath; VES couplet; pitting oedema